Lake of fire ebook - Fairbairn, Nathan (Lake of Fire (2016)., 2018)
It is 1220 AD, and the gears of the Albigensian Crusade grind on. When an alien spacecraft infested with a horde of bloodthirsty predators crash-lands in the remote wilderness of the French Pyrenees, a small band of crusaders and a Cathar heretic are all that stand between God's Kingdom and Hell on Earth. Collects LAKE OF FIRE #1-5.. Author: Nathan Fairbairn. Illustrator: Matt Smith . 2017 Nathan Fairbairn.